Pelaksanaan Regulasi Pemerintah Atas Pemberlakuan Asean China Free Trade Agreement (ACFTA) Terhadap Kelangsungan Usaha Mikro Kecil Menengah di Kota Pekanbaru - Ade Pratiwi Susanty (Jurnal Selat, 2014)
International legal instruments governing trade relations between countries is contained in documents the GATT (General Agreement on Tariffs and Trade) countries signed in 1947, and entered into force since 1948.From time to time the provisions of GATT negotiations enhanced through a range of rotation, the last through the Uruguay Round negotiations that succeeded in forming an organization of world trade (World Trade Organization / WTO). International economic organizations in addition to the WTO there are also regional organizations, namely the ASEAN-China Free Trade Agreement (ACFTA). ACFTA Agreement is a trade agreement between ASEAN countries on the State of China. ACFTA has been effectively running in January 2010. The legal basis of the ACFTA is the Framework Agreement on Comprehensive Economic Cooperation Between the Association of Southeast Asian Nations and the People’s Republic of China, which was signed by the President of the Republic of Indonesia (Megawati) on December 4 Novenber 2002 in Phnom Penh, Cambodia, and has been ratified by the President Republic of Indonesia through the Decree of the President of the Republic of Indonesia Number 48 Year 2004 on Ratification of the Framework Agreement on Comprehensive Economic Cooperation Between the Association of Southeast Asian Nations and the People’s Republic of China (Framework Agreement). The implementation of ACFTA in 2010 marked the entry of Chinese goods are flooding the Indonesian region, including the city of Pekanbaru greatly affect domestic goods produced by Micro, Small and Medium Enterprises (SMEs) Pekanbaru. The influx of goods from China makes more and more choice for the consumer goods Indonesian. The prices of goods from China are relatively inexpensive and varied lead Indonesian consumers prefer and buy goods from China. This resulted in a decline in the goods manufactured by Micro, Small and Medium Enterprises (SMEs). Keywords: International Trade, ACFTA Agreement, Micro, Small and Medium Enterprises